Dynamic analysis of an improper fractional-order laser chaotic system and its image encryption application. (June 2020) - Yang, Feifei; Mou, Jun; Ma, Chenguang; Cao, Yinghong
Highlights: An improper fractional-order laser chaotic system is constructed. The improper fractional-order laser chaotic system is digital circuit implemented by DSP platform. An image encryption algorithm based on improper fractional-order laser chaotic system is proposed. Simulation results and performance analysis demonstrate the security and robustness of the proposed algorithm. Abstract: The fractional-order chaotic systems have characteristics of the all chaotic systems, however, the improper fractional-order chaotic systems have more complexity random sequences, which more suitable for chaotic cryptosystems. To investigate the application of improper fraction order chaotic system in chaotic cryptography, in this paper, an improper fractional-order laser chaotic system is constructed and applied in image encryption algorithm. The dynamic performances of the system are studied through phase diagrams, Lyapunov exponents spectrum, bifurcation diagrams and C 0 complexity. Meanwhile, the improper fractional-order laser chaotic system is realized based on DSP platform. In addition, the performances of the designed encryption scheme are analyzed by key space, correlation coefficients, information entropy, histogram, differential attacks and robustness analysis. The experimental simulation results indicate that the improper fractional-order laser chaotic system not only has the abundant dynamic characteristics, but also has better security when it is used to image encryption algorithm. Therefore, this research would provide theoretical basis for the improper fractional-order laser chaotic system in security communications application.